2018
DOI: 10.2217/cns-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of ERC1671 plus bevacizumab versus bevacizumab plus placebo in recurrent glioblastoma: interim results and correlations with CD4 + T-lymphocyte counts

Abstract: Aim:ERC1671 is an allogeneic/autologous therapeutic glioblastoma (GBM) vaccine – composed of whole, inactivated tumor cells mixed with tumor cell lysates derived from the patient and three GBM donors.Methods:In this double-blinded, randomized, Phase II study bevacizumab-naive patients with recurrent GBM were randomized to receive either ERC1671 in combination with granulocyte-macrophage colony-stimulating factor (GM-CSF) (Leukine® or sargramostim) and cyclophosphamide plus bevacizumab, or placebo plus bevacizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…On the basis of these trials, clinical trials of combination treatments with GM-CSF with EGFRvIII peptide vaccine and bevacizumab have shown that this combination improved progression-free survival in GBM patients compared with single-modality treatment [135]. Similarly, the preliminary results of a phase II clinical trial of combination treatment with GM-CSF with cyclophosphamide and bevacizumab, as well as results from a phase I trial of combination treatment with MK-1454 (stimulator of IFN gene agonist) and pembrolizumab, and results from a completed trial of Toca 511 and Toca FC, have shown that these treatments increased survival rates in GBM patients [136,137].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 97%
“…On the basis of these trials, clinical trials of combination treatments with GM-CSF with EGFRvIII peptide vaccine and bevacizumab have shown that this combination improved progression-free survival in GBM patients compared with single-modality treatment [135]. Similarly, the preliminary results of a phase II clinical trial of combination treatment with GM-CSF with cyclophosphamide and bevacizumab, as well as results from a phase I trial of combination treatment with MK-1454 (stimulator of IFN gene agonist) and pembrolizumab, and results from a completed trial of Toca 511 and Toca FC, have shown that these treatments increased survival rates in GBM patients [136,137].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 97%
“…369 Bota et al (University of California Irvine, Irvine, CA, USA) reported that combining an allogeneic/autologous vaccine (ERC1671) with recombinant colony stimulating factor 2 (CSF2, best known as GM-CSF), cyclophosphamide and bevacizumab (a monoclonal antibody specific VEGFA) 205 results in a clinically-relevant survival benefit in glioblastoma patients (12 months vs. 7.5 months for patients receiving bevacizumab only). 370 Kanekiyo and colleagues (Yamaguchi University Graduate School of Medicine, Yamaguchi, Japan) combined a vaccine based on 5 HLA-A*24:02-restricted peptides with oxaliplatin in patients with colorectal cancer, finding humoral responses to multiple peptides that were associated with cytotoxic T-cell responses and/or improved overall survival (OS). 371 Geyer and collaborators (Memorial Sloan Kettering Cancer Center, New York, NY, USA) employed CD19-targeting chimeric antigen receptor (CAR) T cells in patients afflicted by residual CLL upon chemotherapy with pentostatin (is a purine analog that inhibits nucleic acid synthesis), cyclophosphamide and rituximab (a CD20targeting monoclonal antibody).…”
Section: Finalized Clinical Studiesmentioning
confidence: 99%
“…Importantly, arguing against its putative positive immunomodulatory role, standard therapy induces systemic immunosuppression and long-lasting severe lymphopenia [178,179,180,181,182,183,184,185,186,187], and may interfere with the immunotherapy/oncolytic virotherapy efficacy, which is critically dependent on the activity of the host’s own immune cells [10,159,188,189,190,191,192,193,194,195,196,197]. In support of this, recent studies have reported that high blood CD3+/CD4+ T cells counts [159] and tumor-infiltrating lymphocyte density [188] were correlated with better overall survival in glioblastoma patients receiving dendritic cell vaccination, while adjuvant TMZ hampered a CD8+ T cell count increase and the generation of CD8+ T cell-associated antitumor memory promoted by dendritic cell vaccination [198]. Standard therapy differentially affects the immune system of each patient [198,199,200], and patients with less severe standard therapy-induced immune suppression might derive more benefit from immunotherapy/oncolytic virotherapy than severely immunosuppressed patients.…”
Section: Is a Benefit Derived From Immunotherapy/oncolytic Virothementioning
confidence: 99%